Declining Acquisitions Budgets: Allocation, Collection Development, and Impact Communication, 1st edition - Lee, Sul H. (Routledge, 2020)
This book, first published in 1993, is a key resource in beginning the task of re-thinking traditional methods of collection development and maintenance. The contributing authors to this volume provide thought-provoking chapters which touch on library, business, and societal issues as related to work as a library administrator. They advise on how to take a more economical approach to developing and maintaining a great collection - with a smaller budget.